2023
DOI: 10.1088/2515-7620/acac03
|View full text |Cite
|
Sign up to set email alerts
|

Launching criteria of ‘Heatstroke Alert’ in Japan according to regionality and age group

Abstract: To reduce heatstroke cases, the Japanese government launched “Heatstroke Alert” in 2020. In this initiative, an alert is issued when the daily maximum wet bulb globe temperature (WBGT) is expected to reach or exceed 33 °C. However, heatstroke incidents at a daily maximum of WBGT of 33 °C can vary by regions and by age groups. In this study, we analyzed the heatstroke incidence in all 47 prefectures of Japan at the daily maximum WBGT of 33 °C, considering age groups. In addition, considering variations in heats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Growing awareness of global warming and heat‐related risks has prompted people to adopt effective strategies to avoid excessive heat exposure, engage in cooling behaviours and ensure adequate water intake 47 . Notably, the Japanese government's ‘Hot Temperature Alert’ initiative, launched in 2011, 48 advises individuals, particularly vulnerable groups such as pregnant women, to refrain from outdoor activities and take proper cooling measures. These efforts at individual and societal levels in Japan have likely reduced the risk of dehydration and weakened the association between high temperatures and PTBs.…”
Section: Discussionmentioning
confidence: 99%
“…Growing awareness of global warming and heat‐related risks has prompted people to adopt effective strategies to avoid excessive heat exposure, engage in cooling behaviours and ensure adequate water intake 47 . Notably, the Japanese government's ‘Hot Temperature Alert’ initiative, launched in 2011, 48 advises individuals, particularly vulnerable groups such as pregnant women, to refrain from outdoor activities and take proper cooling measures. These efforts at individual and societal levels in Japan have likely reduced the risk of dehydration and weakened the association between high temperatures and PTBs.…”
Section: Discussionmentioning
confidence: 99%
“…The regression coefficients a i and b i in equation (3) were estimated for each age group using a generalized linear model with a quasi-Poisson distribution in R. Long-term trends and seasonality were not controlled for in this calculation because Oka et al (2023b) demonstrated that although the explanatory variable in equation ( 3) was the WBGT, these treatments did not cause substantial differences in the value of a i between the non-control and control cases.…”
Section: Heat-related Health Impacts 231 Development Of Heatstroke Pr...mentioning
confidence: 99%
“…To address the escalating challenge of heat stress, HHWS has been adopted in various cities across North America and Europe, although the specific features of these systems may vary to accommodate local climate conditions and the vulnerability of the population (Kotharkar and Ghosh 2022). In Japan, a similar HHWS was established in 2011, where a heat warning is triggered when the maximum temperature reaches or exceeds 35 • C (Oka et al 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…These studies propose the use of heat stress indicators (HSIs), which comprehensively consider multiple climate variables, with a particular emphasis on the combined impact of T air and humidity. As a result of this research progress, the Japanese government has made notable revisions to the HHWS in Japan (Oka et al 2023a). Specifically, the exposure indicator has shifted from T air to Wet Bulb Globe Temperature (T WBG ), and the updated system has been carried out for the whole country since 2021 (Liljegren et al 2008, JMA & MOE 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation